SISTEM INFORMASI PENJUALAN PADA KANTIN STUDIO ANIMASI (STUASI) AIKOM BERBASIS WEBSITE - Safrudin sukarmin; Aswin Abbas; Akil Talib (JAMINFOKOM - Jurnal Manajemen Informatika dan Komputer, 2022)
The amount of effort that every human being makes in various sales, both traditional and modern, makes people do various ways by utilizing existing technology. One of the activities carried out is to use internet or online media in developing sales or better known as e-commerce, for example selling handmade goods through websites. Based on the description above, the author tries to create a website design for selling food and beverages at the AIKOM animation studio canteen (STUASI) which aims to promote and provide information about products, product prices and product details for handmade goods quickly and updated. The use of the website is expected to expand the reach of product marketing, so as to increase sales. This web-based sales system was developed using the waterfall development method, with PHP programming language and MySQL database used. It is hoped that the handmade goods sales system using this website can reduce the costs incurred for product marketing and promotion and be able to increase the marketing and sales activities of handmade goods to be more effective and efficient.